E-Learning Amidst the Pandemic: Teachers’ Perspective in the Philippines - Armmagideon Estrellan; Kenneth John Ferrariz; Patricia Ann Lazona; Viance Elmer Madres; Joselyn C. Estrellan (Universitas Pendidikan Indonesia (UPI), 2021)
The purpose of this study is to explain in detail the perspectives of teachers and the challenges that the stakeholders of the E-learning process may face in the conditions of the COVID-19 pandemic. The respondents of this study were 5 teachers at the ACCESS campus of the Sultan Kudarat State University (SKSU), the Philippines. This study used a semi-structured interview method to obtain the necessary data which was analyzed using thematic analysis. The study revealed that teachers recognized this new mode of learning as a more comfortable and convenient way to use; however, assessing student learning and interacting with them was in general difficult. Thus, operational and psychological challenges are experienced by teachers in adapting to the new learning model. The results of the analysis revealed that SKSU administrators must provide broad assistance to all teachers, especially regarding the challenges they face at this time, besides that, teachers and students must be trained and ready to use sophisticated e-learning technology.